The World Trade Organization’s response to renewable energy support policies: limitations and challenges - Kroetz, Maria Eugênia do Amaral (2020)
Renewable energies have gone through transformations, involving market, environmental and technological aspects. However, doubts remain on how international regulatory regimes have addressed these changes. This Master’s thesis aims to investigate the World Trade Organization (WTO)’s response to renewable energy support policies from producing countries of solar and wind power technology and equipment. The research’s primary argument is that, through the interpretation of the WTO Dispute Settlement Body, the multilateral trading system has been open to traditionally non-trade values, such as climate change, without losing sight of its classical liberalization principles. The work recognizes the limitations of the interpretation from the Dispute Settlement Body and makes the case for WTO Subsidy Law reform. It recognizes the challenges involving the (re)negotiation of the multilateral trade regulation. Being in a Law and Development Master Program and, as the issue at hand relates to global challenges, factual elements of the renewable energy sector matter to this research. Therefore, the thesis proposes an approach that considers the economic, political and legal angle of the renewable energy sector. In this way it delineates the premises deemed essential to investigate the WTO’s response to renewable energy support programs. The research is set against a conflicting background that involves different layers of international obligations and driving interests considered by States when implementing public policies. The thesis first presents the state of the art of the discussion on renewable energy policies from wind and solar power producing countries. Then it concentrates in legal aspects of the issue proposed, investigating the specific elements from WTO Agreements, the United Nations climate change regime and WTO Dispute Settlement Body cases on renewable energy. Finally, the research presents the way forward for WTO subsidy rules reform considering the change of expectations from the Membership in the case of renewable energy programs.